2012
DOI: 10.1097/cej.0b013e328351c775
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity and the risk of colorectal adenoma

Abstract: Inconsistent results regarding the association between abdominal obesity and the risk of colorectal adenoma (CRA), the precursor of colorectal cancer (CRC), have been reported. To provide a quantitative assessment of this relationship, we summarized the evidence from observational studies in categorical, linear dose-response meta-analyses. We searched MEDLINE and EMBASE for studies of waist circumference (WC) and/or waist-hip ratio (WHR) and CRA risk published until the end of October 2011. Summary relative ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 40 publications
3
27
1
1
Order By: Relevance
“…Other studies reported that cigarette smoking was associated with abdominal and visceral obesity [31,32]. However, our observation didn’t support such finding, and there was a little trend towards a higher prevalence in abdominal obesity with smoking, but not statistical significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies reported that cigarette smoking was associated with abdominal and visceral obesity [31,32]. However, our observation didn’t support such finding, and there was a little trend towards a higher prevalence in abdominal obesity with smoking, but not statistical significant.…”
Section: Discussioncontrasting
confidence: 99%
“…33–36 Although the results were expressed differently (BMI per 5-unit increase,33 BMI cut-off value35 36 or 10 cm increase in waist circumference34), all showed a small but significant association, with similar trends across races, country of origin, measured or self-reported BMI, and site other than rectal adenoma. The significance of the association persisted after adjustment for physical activity, family history of CRC, energy or alcohol intake, smoking habits or non-steroidal anti-inflammatory drug use (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A similar trend is observed with reference to colorectal adenomas. BMI was found to be an independent risk factor for advanced colorectal adenomas [17,18]. A significant correlation was found between BMI and CRC location.…”
Section: Discussionmentioning
confidence: 75%